Glicerina bruta substituindo o milho em dietas de baixo amido na terminação de cordeiros - Carvalho, Vanessa Barbosa de [UNESP] (2015)
This study aimed to evaluate the effects of crude glycerin (GB) inclusion until 30% of DM in diets with high level of concentrated and low starch, replacing total maize of lambs feedlot diet on intake, digestibility, feeding behavior, blood parameters, performance, carcass characteristics, quality and fatty acid profile of meat. Forty animals with 23.5 ± 1.35 kg initial body weight were distributed in a randomized block design with five treatments. The treatments were: no inclusion of GB; inclusion of 7.5% of GB; inclusion of 15% GB; inclusion of 22.5% and inclusion of 30% GB on DM basis. The roughage used was Tifton 85 hay at 18.19% and the concentrate (81.81%) was composed of corn, GB, corn gluten meal, corn oil, urea, sunflower meal, soybean hulls and mineral salt. Duration of experiment was on average 72 ± 7 days, and the animals were slaughtered around 38 kg of body weight. The procedure used for data analysis was the SAS program and the treatment effects were decomposed into linear, quadratic contrasts, as well as the effect of diet with 0% vs. GB (average of all treatments containing GB). The contrasts were considered significant when P ≤ 0.05 and trend when P> 0.10. The DM and nutrientes intake were not affected by GB (P> 0.10) except for NDF intake that decreases linearly in feeding behavior and performance with increasing GB (P = 0.01). The DM, OM and CP increased linearly with inclusion of GB and EE digestibility showed a quadratic behavior (P = 0.01). In the feeding behavior trail, time spent for rumination and intake+rumination on min/g NDF increased linearly with inclusion of GB (P ≤ 0.02). Blood parameters and animals performance had no significant differences (P ≥ 0.11). The weight and yield of hot and cold carcass linearly decreased with the inclusion of crude glycerin (P ≤ 0.02). The AOL, EGS, weight and yield of omental, mesenteric and renal fat had no differences with the inclusion of GB (P ≥ 0.14). The ...